The Roman Building at Via Brisa: a Sector of the Imperial Palace in Milan (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
This contribution wants to reconsider the interpretation of the roman building in Via Brisa, one of the sectors of the Imperial palace in Milan, dated between the end of the IV and the V century A.D. A review on the past studies and some observations about the internal circulation will give the opportunity to riconsiderate the general interpretation of the entire structure, which can be interpreted as a luxurius sector belonging to the Imperial palace of Milan, organized in “apartments” and used for high-reception functions.
Keywords: Cubiculum; Late Antiquity; Imperial palace; Roman Milan; Roman architecture; Triclinium; Vestibule; Villa